Boundary condition effects on postbuckling response of functionally graded hybrid composite plates - Vummadisetti, Sudhir; Singh, S.B. (Journal of Structural Engineering, 2024)
Boundary conditions are one of the key parameters that have a significant effect on postbuckling response. In the currentpaper, flexural and in-plane boundary conditions are considered to study their effects on buckling and postbucklingresponses of functionally graded hybrid plate with and without cutouts subjected to positive and negative in-planeshear loads. The quasi-isotropic (±45/0/90)2s layup sequence is considered in the plate for the numerical investigationwith various shaped cutouts. The flexural boundary conditions include all four edges simply supported, two edgessimply supported, and two edges clamped, and all four edges clamped while the in-plane boundary conditions aresimply supported on all edges with different in-plane boundary restraints. The analysis is based on finite elementmethod-based software ABAQUS. Postbuckling strength is predicted by non-linear analysis static-riks method inwhich geometric imperfections are incorporated and the first failure is predicted by Tsai-Hill failure criterion. Theeffect of flexural and in-plane boundary conditions on postbuckling strength of composite plates is explained distinctly.Buckling and postbuckling strengths are observed to be higher in plates with all edges clamped while it is lower in caseof plates with all edges simply supported in case of flexural boundary conditions. PBC1 in-plane boundary restraintis having high buckling and postbuckling strengths amidst all in-plane boundary conditions. Though plates withoutcutout have higher buckling capacity, it is worth noting that functionally graded hybrid composite plate with diamondshaped cutout can resist higher in-plane shear buckling load than other shaped cutouts for both flexural and in-planeboundary conditions.